Peran mahasiswa dalam mendukung proses audit sesuai standar profesional akuntan publik - Muhammad Faqiha Putro; Lutfi Setyowati; Ista Lintang Kinanthi; Yordanius Riski Rivaldo (Department of Accounting Universitas PGRI Yogyakarta, 2026)
This internship aims to provide students with practical experience in understanding the audit process in accordance with the Public Accounting Professional Standards (SPAP). This internship explores students' roles in supporting audit implementation through direct involvement in financial statement audits, preparation of audit working papers, account reconciliations, substantive testing, and preparation of compiled financial statements. The approach used in this article is descriptive qualitative, employing direct observation and participation during the internship. The results of the activity indicate that student participation can improve the effectiveness and efficiency of the audit process, while deepening students' understanding of audit procedures, professional ethics, and the application of Financial Accounting Standards (SAK) and Auditing Standards (SA). In addition, several challenges that frequently arise in client entities were identified, including internal control weaknesses, inconsistencies in fixed asset recording, a lack of CKPN (Current Impairment Allowance), and errors in income tax calculations. This internship program also provides students with professional experience in adapting to the audit work environment and improving their technical and administrative competencies. Thus, the internship at KAP Sumardi serves as a strategic tool to prepare accounting students to enter the professional workforce in auditing and accounting